Research on the Acoustic Scattering Characteristics of Multi-Sections Conning Tower Geometries in Monostatic Configuration - HAN, Lin-Jiang; SONG, Hao; CHEN, Chang-Xiong; PENG, Xi-Rui; PENG, Zi-Long (Archives of Acoustics, 2022)
The overall acoustic echo of a submarine is greatly dependent on the conning tower. For enhancing the acoustic stealth performance of a submarine, it is necessary to research an innovative design scheme of the conning tower to reduce its target strength (TS). The aim of this work is to reduce the TS of a conning tower by varying its geometry and streamlining. The accuracy in modelling the acoustic scattering of a conning tower using the Kirchhoff approximation (KA) was validated, compared with finite element analysis (FEA). Several angular conning tower geometries were designed to analyze the effect of streamlining and the number of lateral facets on TS using the KA method. In consideration of the actual situation, the acoustic effect of backing medium was analyzed by compared water-filled elastic hulls with rigid hulls. From the observed TS calculation results, it is shown that the non-streamlined four lateral-facet conning tower geometries are optimal for acoustic stealth performance during the range of incidence angles from −10° to 10°, whereas the streamlined versions have better performance at incidence angles beyond this range. Furthermore, elastic hulls and rigid hulls provide similar spatial distribution regularities in monostatic configuration with the rigidity affecting the magnitude of the TS.